The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/genes14010236
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of PKCγ Genetic Variants—Possible Function as a Non-Invasive Diagnostic Biomarker in Ovarian Cancer

Abstract: Ovarian cancer has the highest mortality rate among gynecologic malignancies, owing to its misdiagnosis or late diagnosis. Identification of its genetic determinants could improve disease outcomes. Conventional Protein Kinase C-γ (PKCγ) dysregulation is reported in several cancers. Similarly, its variant rs1331262028 is also reported to have an association with hepatocellular carcinoma. Therefore, the aim of the present study was to analyze the variant rs1331262028 association with ovarian cancer and to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Genomic DNA extraction and SNP analysis. The method used for Genomic DNA extraction was the phenol-chloroform method 8,18 . ARMS-PCR was performed to detect single nucleotide change in PRKCI.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA extraction and SNP analysis. The method used for Genomic DNA extraction was the phenol-chloroform method 8,18 . ARMS-PCR was performed to detect single nucleotide change in PRKCI.…”
Section: Study Populationmentioning
confidence: 99%
“…SNPs in the genes GRIK1, MICA, HLA-DQA/DQB, and KIF1B have been reported to be associated with the risk of HCC 5 . The PKC family proteins have been positively associated with HCC in several studies 6 8 . However, those studies usually indicated its involvement in the carcinogenic process at a functional level.…”
Section: Introductionmentioning
confidence: 99%
“…Although NQO1 can protect normal cells from oxidative stress, it has been reported that a high expression of NQO1 at the early stages of carcinogenesis can favor cancer cell growth [4][5][6]. The clinical research is always focused on finding novel biomarkers for prognostic purposes as well as therapeutic targets since they are of crucial importance to improve the outcome of patients affected by aggressive neoplasms [7][8][9][10][11][12][13]. It has been reported that NQO1 is highly expressed in many solid tumors such as uterine cervix [14], endometrium [14], lung [15] colon [16], pancreas [17] and ovarian cancer [18].…”
Section: Introductionmentioning
confidence: 99%